Skeletal muscle PLIN3 and PLIN5 are serine phosphorylated at rest and following lipolysis during adrenergic or contractile stimulation. Issue 4 (17th September 2013) - MacPherson, Rebecca E. K.; Vandenboom, Rene; Roy, Brian D.; Peters, Sandra J.
Abstract In adipose tissue, access of adipose triglyceride and hormone‐sensitive lipases (ATGL and HSL) to the lipid droplet depends on PLIN1 phosphorylation, however, PLIN1 is not expressed in skeletal muscle and the phosphorylation of the expressed PLINs has yet to be investigated. Further, direct interactions between skeletal muscle PLINs and HSL are unknown. We investigated the isolated and combined effects of epinephrine and contraction on PLIN‐to‐lipase interactions as well as phosphorylation. Isolated rat solei were assigned to one of four 30 min in vitro conditions (25°C): (1) rest; (2) intermittent tetanic stimulation (60 Hz for 150 msec; train rate 20/min); (3) 5 nmol/L epinephrine; (4) intermittent tetanic stimulation and 5 nmol/L epinephrine. Immunoprecipitation of serine phosphorylated proteins followed by Western blotting for PLIN2, PLIN3, PLIN5, revealed that only PLIN2 is not phosphorylated under any of the experimental conditions. This is the first study to show that in whole rat skeletal muscle PLIN3 and PLIN5 are serine phosphorylated. The degree of serine phosphorylation remained unchanged following adrenergic and/or contractile stimulation. Oil red O staining of muscle sections for lipid content shows a significant decrease following each condition, confirming lipolysis occurred (P < 0.05). PLIN2, 3, and 5 all interact with HSL and ATGL, but these interactions were unchanged following treatments. Our results show that in skeletal muscle, PLIN2 is not serine phosphorylated at rest or with lipolytic stimulation and that while PLIN3, PLIN5 are serine phosphorylated at rest, the degree of phosphorylation does not change with lipolytic stimulation.